Bacillus Spores in the Food Industry: A Review on Resistance and Response to Novel Inactivation Technologies. Issue 6 (3rd October 2016) - Soni, Aswathi; Oey, Indrawati; Silcock, Pat; Bremer, Phil
Abstract: The importance and challenges presented by Bacillus spores in the food industry are briefly outlined with a focus on Bacillus cereus . The structure and the mechanism of resistance exhibited by Bacillus spores are described, and the steps involved in their germination are included. Novel technologies, using no or only mild heat treatments, to inactivate Bacillus spores are covered, including ultraviolet radiation, pulsed electric field, and high‐pressure processing, both as stand‐alone techniques or techniques as part of a hurdle approach.